DEVELOPMENT OF AN ELECTRIC BICYCLE FOR A SHARING SYSTEM IN PRAGUE - William Deleenheer; Lukáš Jáneš; Akshaya Jayakumar (Acta Polytechnica CTU Proceedings, 2017)
By means of a development of an e-bike sharing system the Electromobility Project wants to provide an alternative way of comfortable transportation for students and staff of the CTU, primarily to commute between different campuses. The research for this project contains at least three different fields of study, namely electric vehicle and docking station development, intelligent transport systems and management and economics of transportation and telecommunication. After briefly stating general requirements for the sharing system, this paper focuses on the development of the electric bicycle. First an ideal bike design is defined. Then necessary motor power and battery capacity are calculated by estimating characteristics of cycling in Prague. A prototype was developed by converting a normal bicycle to an electric bicycle. Being equipped with devices for e-bike monitoring, controlling and data recording for a post trip analysis, this prototype is also intended to have an educational value for future students in the project. Results consist of an electrical bicycle configuration that matches the requirements and a sketch of an ideal e-bike for this project.